Do economic preferences of children predict behavior? - Laura Breitkopf; Shyamal K. Chowdhury; Shambhavi Priyam; Hannah Schildberg-Hörisch; Matthias Sutter (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2020)
Economic theory and empirical evidence establish that economic preferences predict behavior and life outcomes for children, adolescents, and adults. In this paper, we use novel data on 4,282 siblings aged 6 to 16 that combine incentivized measures of time, risk, and social preferences with comprehensive information on child behavior and family environment. Using standard cross-sectional specifications, our results confirm the predictive power of children's preferences for behavior. However, when estimating household fixed effects models that allow controlling forall characteristics that are shared by siblings, this predictive power largely vanishes. We discuss implications for research on children's preferences and behavior.
Keywords: C91; D01; J13; 330; time preferences; risk preferences; social preferences; experiments with children; origins of preferences; human capital; behavior; household fixed effects; siblings